Prevención del abuso sexual y el maltrato infantil utilizando un modelo virtual - Hernando Tamayo, Luis (Universidad Santiago de Cali, 2017)
This research was designed to develop a virtual model aimed to the prevention of sexual abuse and child abuse. Where it is intended that children acquire skills for self-protection and self-care of their body and they know how to identify different risky situations and what to do if they are in one of these situations. Such virtual tool was implemented and compared with the tradi-tional way in which they have been working the transversal project of sex education focused on the prevention of child sexual abuse, and finding that by using a virtual model generated a greater impact on participating children, since they were able to identify most risky situations and in the same way, they set different options for self-protection. Likewise research showed those things that children are afraid to tell due to different factors fears.